2012
DOI: 10.5539/ijbm.v7n20p120
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Strategy: A New Strategy for Competitive Advantage

Abstract: Both strategic management researchers and practitioners have realized the importance of cost and differentiation strategies for effective organizational performance and excellence. Recently many large enterprises/corporations have been applying both strategies simultaneously, rather than applying a single strategy at one period of time. The implementations of the three strategies are commonly used by the big corporations involved in domestic, regional, international and global business. This article has three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 30 publications
1
20
1
1
Order By: Relevance
“…About 43% of respondents believe that the issue of infrastructure is a primary one, particularly for science based qualifications, in the form of e-learning infrastructure, laboratories and other important apparatus and in this competitive market, where the markets are not just local but global. Findings support Boroto et al, (2012) who concluded that a new trend in higher education is linked with high investments in new technologies, modern libraries and students' campuses. Other product factors respondents considered critical in differentiating a tertiary education institution for competitive advantage stress the need for unique / accredited programmes (25%), extra curriculum activities (14%), offering of practical than theoretical courses (9%) and provision of research resources (11%) among others as presented in Figure 4.2.…”
Section: Methodssupporting
confidence: 55%
“…About 43% of respondents believe that the issue of infrastructure is a primary one, particularly for science based qualifications, in the form of e-learning infrastructure, laboratories and other important apparatus and in this competitive market, where the markets are not just local but global. Findings support Boroto et al, (2012) who concluded that a new trend in higher education is linked with high investments in new technologies, modern libraries and students' campuses. Other product factors respondents considered critical in differentiating a tertiary education institution for competitive advantage stress the need for unique / accredited programmes (25%), extra curriculum activities (14%), offering of practical than theoretical courses (9%) and provision of research resources (11%) among others as presented in Figure 4.2.…”
Section: Methodssupporting
confidence: 55%
“…(3) A new proposed model and perspective as an alternative to the generic typology of competitive strategies theory (Baroto et al, 2012). As a result of these efforts, hybrid strategies have gained increasing recognition, in addition to their logical feasibility (Claver-Cort es et al, 2012;Baroto et al, 2012;Alnoor et al, 2022).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…(2) There is an effort to distinguish internal and external conditions and the sector applicability of the Porter (1980) competitive strategy and limit the boundaries of the theory (Anwar and Hasnu, 2017a). (3) A new proposed model and perspective as an alternative to the generic typology of competitive strategies theory (Baroto et al. , 2012).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…As global competition increases, the formation of this business hybrid is very important. Baroto et al (2012) in their research on hybrid strategies stated that this hybrid strategy was able to increase the company's ability to adapt quickly to environmental changes and encourage the learning of new skills and technologies.…”
Section: Hybrid Businessmentioning
confidence: 99%